An interaction analysis model to study knowledge construction in xMOOCs - Saadatdoost, Robab; Hiang Sim, Alex Tze (Letters in Information Technology Education (LITE), 2022)
One of the recent tools of online teaching and learning has been MOOC which utilizes the web and can be considered a critical factor in delivering future lessons. Coursera is an approved and famous online learning tool established by two professors from Stanford. According to previous studies, Coursera concentrates on duplicating knowledge instead of constructing it. The present work aims at observing Coursera community in its normal context and investigating how participants construct knowledge. The required data were gathered through archive data including the top and chosen posts of online discussion groups. The interaction analysis model (IAM) was used to qualitatively analyze the data. In the observed courses, it was found that Coursera is mostly at Phase I (sharing/comparing information) of the IAM. Using the IAM which was first proposed for investigations of online debates, the research found a new phase and operations for assessing the level of knowledge construction in online discussion forums. This research bridges the gaps in the related literature by providing a foundation for understanding knowledge construction in the xMOOC context. Besides, this research developed understanding for future work which is a Coursera community framework that generally makes a MOOC community more potential to construct knowledge.